Quantification of PET and CT Misalignment Errors Due to Bulk Motion in Cardiac PET/CT Imaging: Phantom and Clinical Studies - Pardis Ghafarian; Mohammad Reza Ay; Armaghan Fard-Esfahani; Arman Rahmim; Habib Zaidi (Frontiers in Biomedical Technologies, 2014)
Purpose: Non simultaneous acquisition between CT and PET module can introduce misalignment artefact in cardiac PET/CT imaging due to patient motion. We assessed the clinical impact of patient motion and the resulting mismatch between CT and corresponding CT-based attenuation corrected (CTAC) PET images on apparent myocardial uptake values in cardiac PET/CT imaging. Methods: The evaluation of patient motion was performed using clinical and experimental phantom studies acquired on the Biograph TP 64 PET/CT scanner. In order to simulate patient motion, CT images were manually shifted from 0 to 20 mm in steps of 5-mm in six different directions. The reconstructed PET images using shifted CT were compared with the original PET images. The assessment of PET images was performed through qualitative interpretation by an experienced nuclear medicine physician and through quantitative analysis using volume of interest based analysis. Moreover, Box and Whisker plots were calculated and bull’s eye view analysis performed. PET images were also reoriented along the short, horizontal and vertical long axis views for a better qualitative interpretation. Results: A 20-mm shift in the right direction between attenuation and PET emission scans produced mean absolute percentage difference in uptake values in the lateroanterior (33.42±9.07) and lateroinferior (27.39±10.43) segments of the myocardium. Conclusion: Misalignment could introduce artifactual nonuniformities in apparent myocardial uptake value and the variations were more significant for the misalignment toward the right, feet and head directions, in such a way that even with a 5-mm shift in the CT image, errors in interpretation of PET images could occur. Furthermore, errors in PET uptake estimates were observed for movements as large as 10-mm in the left, posterior and anterior directions.